PENGABDIAN MASYARAKAT EDUKASI PHBS DAN PENGELOLAAN SAMPAH MELALUI KREATIVITAS DAUR ULANG GALON DI DESA WIRUN, KECAMATAN MOJOLABAN, KABUPATEN SUKOHARJO - Zidan Wijaya Sakti; Ulande Dikara Chelsyannisa Sila; Hanifa Ardhiansari Hasanah; Handika Aji Fauzia Maghfirotul Sabilla; Isniasta Eka Putri; Aulia Mulyasa Insani; Kamila Kamila; Titis Herina Utami; Aprilia Bunga Lestari; Naila Berlian Nur Rahma; Zuhrufa Amania Sholehah; Nabila Lintang Dikmazari (Universitas Muhammadiyah Surakarta, 2026)
The main issue faced in Wirun Village is the low level of awareness among the community, particularly children, in practicing Clean and Healthy Living Behaviors (PHBS) and managing waste wisely, despite the availability of waste collection facilities. To address this issue, a team of students from the Community Service Program (KKN) at Muhammadiyah University of Surakarta initiated an educational program on PHBS, combined with a creative learning activity involving the recycling of used plastic bottles. The implementation method consists of three stages: planning, execution, and evaluation. The activities were conducted through interactive education, handwashing practice, waste sorting, educational games, and a painting competition using pots made from used plastic bottles. The results of the activities showed an increase in children's understanding of PHBS and waste management, as evidenced by participants' enthusiasm, their ability to distinguish between types of waste, and good teamwork in the painting competition. Evaluations through observation and games demonstrated that a participatory and creative educational approach significantly enhances children's memory and understanding. The conclusion from this activity is that the educational program successfully achieved its objectives and has great potential for sustainable implementation. It is recommended that similar activities be conducted regularly and involve the participation of parents and community leaders to ensure broader and more sustainable impacts.